IMAGE MANAGEMENT MODEL IN COMPANY CRISIS - Bintang Ayu Samniar (Universitas Muhammadiyah Surakarta, 2016)
For the sustainability of the company in Indonesia, triple bottom line concept (people,planet, profit) have to be adding in every company, especially mining company. This concept usually be realized by Corporate Social Responsibility (CSR) department, just like in PT Pamapersada Nusantara (PAMA) District KPCS, East Kalimantan. This research type is descriptive qualitative, which give readers explanation of the situation in facing crisis in 2010 by CSR PAMA KPCS. For explain this, writer used Crisis Pre-Emptive: Image Management Model by Augustine Pang, because the CSR concept which explored by writer is based on crisis which happen there, in 2010. In this study, writer divided the phase into 4 phases as the theory by Pang. They are: Before organizational event: proactive phase; Before organizationalevent: strategic phase; During organizational event: reactive phase; and After organizational event: recovery phase. Writer also make a scheme based on 4 phase above.